Factors Associated with Heating Efficiency in Transcranial Focused Ultrasound Therapy - YAMAMOTO, Kazuaki (Neurol Med Chir (Tokyo), 2020)
Transcranial magnetic resonance-guided focused ultrasound (FUS) therapy is a less invasive stereotactic treatment for tremor and other movement disorders. A sufficiently high temperature in the target brain tissue is crucial during ablation procedures for good outcomes. Therefore, maximizing the heating efficiency is critical in cases where high temperature cannot be achieved because of patient-related characteristics. However, a strategy to achieve the desired therapeutic temperature with FUS has not yet been established. This study aimed to investigate the procedural factors associated with heating efficiency in FUS. We retrospectively reviewed and analyzed data from patients who underwent FUS for ventralis intermedius (VIM) nucleus thalamotomy. In all, 30 consecutive patients were enrolled. 18 with essential tremor (ET), 11 with tremor-dominant Parkinson’s disease (TDPD), and 1 with Holmes tremor. Multivariate regression analysis showed that decline in heating efficiency was associated with lower skull density ratio (SDR) and a greater subtotal rise in temperature until the previous sonication. To maximize heating efficiency, the temperature increase should be set to the least value in the target alignment and verification phases, and subsequently should be increased sufficiently in the treatment phase. This strategy may be particularly beneficial in cases where high ablation temperatures cannot be achieved because of patient-related characteristics. Importantly, a broad patient population would benefit from this strategy as it could reduce the need for high energy to achieve therapeutic temperatures, thereby decreasing the risks of adverse events.